Multidrug Resistance Among Enterococci at a Tertiary Care Hospital in Northern Bulgaria - Hristina Hytkova; Mariya Sredkova; Hristina Hitkova; Kaloyan Ivanov; Vladimir Popov (Journal of Biomedical & Clinical Research, 2013)
Multidrug-resistant (MDR) enterococci are a growing threat. The aim of this study was to determine the species distribution and prevalence of multidrug resistance among 100 enterococcal strains, isolated from patients treated in the University Hospital in Pleven, Bulgaria. Susceptibility to 11 antimicrobial agents was determined, using the disc diffusion method according to the performance standards of Clinical Laboratory Standards Institute (CLS1), 2012. All isolates were screened for high-level aminoglycoside resistance and resistance to vancomycin according to the recommendations of CLS1, 2012. For strains with reduced susceptibility to vancomycin, minimal inhibitory concentrations (MIC) of glycopeptides were determined by Etest (Liofilchem, Italy) and by Vitek 2 automated system. Our results demonstrated decreased susceptibility of enterococci to almost all intensively used anti-enterococcal drugs. Resistance to both penicillins (ampicillin and penicillin) among E.faecium strains was significantly higher (83-87%) than among E.faecalis isolates (4-27%). HLGR was detected in 70% of E.faecium and 38% of E.faecalis isolates. All HLGR strains were foundtobemultiple-drug resistant. Of particular note was the emergence of concomitant resistance to 6 antimicrobials in almost 50% of E.faecium isolates. Despite the wide dissemination of MDR E.faecium strains penicillins in our hospital, acquired resistance to vancomycin was not found.